Case Report: Triple autoimmune overlap: rheumatoid arthritis, systemic lupus erythematosus, and hypereosinophilic asthma with systemic manifestations - Li, Ji; Zhang, Jing; Li, Sheng-Guang; Zhang, Lina; Zou, Yadan; Long, Ting; Yu, Ruohan; Zhang, Yanfeng (Frontiers in Immunology, 2026)
BackgroundOverlap between rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) (“rhupus”) is recognized, but coexistence with a severe eosinophilic asthma syndrome is exceptionally rare. We describe a triple autoimmune overlap of RA, SLE, and hypereosinophilic asthma with systemic manifestations (HASM), initially managed as ANCA-negative eosinophilic granulomatosis with polyangiitis (EGPA) and subsequently re-classified in light of evolving concepts.Case presentationA 44-year-old woman with a 10-year history of seropositive RA developed alopecia, Coombs-positive hemolytic anemia, hypocomplementemia, and ANA and anti-Sm positivity, fulfilling SLE criteria. While receiving prednisone, hydroxychloroquine and conventional DMARDs, she subsequently developed adult-onset asthma, chronic rhinosinusitis with nasal polyps, and marked hypereosinophilia (>3.5×109/L). Secondary causes were excluded; bone marrow showed reactive eosinophilia and ANCA (indirect immunofluorescence and ELISA for MPO/PR3) remained negative. She was diagnosed and treated as ANCA-negative EGPA with high-dose glucocorticoids plus methotrexate and hydroxychloroquine, leading to rapid normalization of eosinophils and durable remission of asthma and sinus disease.DiscussionIn retrospect, and according to the ERS/GERM’O’P proposal, this eosinophilic disorder is best classified as HASM within the EGPA–hypereosinophilic spectrum because ANCA and biopsy-proven vasculitis were absent. The case illustrates the evolving boundary between EGPA and hypereosinophilic syndromes and extends the concept of rhupus to include an EGPA-spectrum eosinophilic asthma syndrome.ConclusionNew-onset eosinophilic asthma in patients with established rheumatic disease should prompt evaluation for EGPA-spectrum or hypereosinophilic disorders. Even when the final label is HASM rather than definite EGPA, timely institution of EGPA-type immunosuppression may avert organ damage.